Vinylphosphonium and 2-aminovinylphosphonium salts – preparation and applications in organic synthesis - Kuźnik, Anna; Mazurkiewicz, Roman; Fryczkowska, Beata (Beilstein Journal of Organic Chemistry, 2017)
The main synthetic routes towards vinylphosphonium salts and their wide applications in organic synthesis are discussed in this review. Particular attention is paid to the use of these compounds as building blocks for the synthesis of carbo- and heterocyclic systems after their prior transformation into the corresponding phosphorus ylides, followed by the intramolecular Wittig reaction with various types of nucleophiles containing a carbonyl function in their structures.
Keywords: 2-aminovinylphosphonium salts; nucleophilic addition; phosphorus ylides; vinylphosphonium salts; Wittig reaction